A Sectoral Approach to the Electricity-growth Nexus in the Eastern Cape Province of South Africa - Dyasi, Poppy; Phiri, Andrew (International Journal of Energy Economics and Policy, 2019)
This paper takes a sectoral, panel approach to investigating the electricity-growth nexus for the Eastern Cape province of South Africa between the period of 2003 and 2017. The empirical investigation was carried out using the Pooled Mean Group (PMG) panel estimators applied to an augmented dynamic growth model whilst the causality tests between electricity consumption and growth where performed using the Dumitrescu-Hurlin (2012) panel non-causality tests. The findings confirm the absence of significant long-run relationship between electricity and growth whilst finding a significant and positive effect over the short-run. Moreover, our causality tests provide strong evidence of causality running from electricity consumption to economic growth hence supporting the “growth hypothesis”. In a nutshell, our results not only demonstrate the importance of performing the electricity-growth analysis at provincial level as opposed to relying on national aggregated estimates but also provides important provincial-specific policy implications and recommendations. Keywords: Electricity consumption; Economic Growth; Provincial. JEL Classifications: C13; C33; C51; Q43 DOI: https://doi.org/10.32479/ijeep.7889